Enolase isoenzymes in uveal melanomas–a possible parameter of malignancy. Issue 4 (April 1983) - Royds, J. A.; Rennie, I. G.; Parsons, M. A.; Timperley, W. R.; Taylor, C. B.
Abstract : Seven uveal melanomas were stained for gamma enolase by an immunoperoxidase PAP (peroxidase-antiperoxidase) technique, and biochemical assays were carried out on tissue homogenates. A correlation between the biochemical assay and the immunoperoxidase staining was demonstrated. Two tumours with the highest biochemical assays showed positive staining for the enzyme, and 2 tumours with the lowest levels showed no appreciable staining. The highest level of enolase was present in a tumour which both clinically and histologically appeared to be benign, and the lowest level occurred in a mixed cell tumour which was large in size; the low level presumably related to its relatively fast rate of growth. Estimation of gamma enolase activity in ocular melanomas may provide an accurate quantitative method for assessing the malignant potential of these tumours.